Perspectivas sobre o teletrabalho no contexto da administração pública brasileira: um anteprojeto - Silva, Gabriella Di Felício Ferreira da (2014)
The job market today, undergoes transformations necessary for employees and employers. Coupled with technological progress, a large degree of connectivity and a new profile of workers opened up many opportunities and relevant aspects that have changed the way of working and their relations in several countries, including Brazil. This technological progress has provided contemporary workers to pursue alternative working outside of the workplace, the office and outside your residence without physical boundaries. Also provided the change in culture of both organizations, as employees, without compromising the Brazilian formal contractual character played by CLT or the Unified Contracting Regime. The emergence of this new type of worker needs to be inserted in the labor market respecting their peculiarities, either by private or public companies. Through a historical review of labor relations and their transformations over time, this research makes a brief reflection and analysis about telework in the Brazilian public administration, implementation, acceptance, advantages, disadvantages, difficulties, external and internal reflections, cultural impact, among others, that this 'new' way of working brings to Brazilian society and the various levels of government.